Aplikasi Metode STIFIn dan ILHAM terhadap Hasil Hafalan Al-QUr`an (Eksperimen terhadap Mahasantri Institut Ilmu Al-Qur`an Jakarta) - Farida, Khusna (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
IIQ Jakarta as an institution that is engaged in tahfizh al-Qur `an need to maintain its existence in the midst of tahfizh institutions that offer fast and qualified memorizing methods. IIQ Jakarta offers not only tahfizh but also academic programs. However, graduate samples in 2016 showed a decrease in the quantity of female memorization. The author conducts experimental research on two modern tahfizh methods that take the theoretical basis of Educational Psychology. The method chosen by the author is STIFIn and ILHAM Method as experimental group and Talaqqi method used in IIQ Jakarta as control group. The authors chose both methods of experiment because it is considered ideal in terms of the duration of memorization time because the two methods do not offer the memorization of too fast and too long. The research method used in this research is experimental method with two manipulated methods and one control method. Tahfizh test results that include quality and quantity are calculated by One Way Anova formula to find out which method is most effective for Pesantren Takhasus IIQ Jakarta. The method was experimented at Pesantren Takhasus IIQ Jakarta by applying the implementation stage of the method and adapted to the situation in Pesantren Takhasus IIQ Jakarta. This study yields the conclusion that out of three methods, ILHAM method is the most effective method applied in PesantrenTakhasus IIQ Jakarta.